Globalization and modernity in Asia : performative moments - Hudson, Chris, 1950-; Barendregt, Bart A., 1968- (Asian visual cultures, 2018)
This series focuses on visual cultures that are produced, distributed and consumed in Asia and by Asian communities worldwide. Visual cultures have been implicated in creative policies of the state and in global cultural networks (such as the art world, film festivals and the Internet), particularly since the emergence of digital technologies. Visual communication and innovation is also thriving in transnational networks and communities at the grass-roots level. This series seeks to explore how the texts and contexts of Asian visual cultures shape, express and negotiate new forms of creativity, subjectivity and cultural politics. It specifically aims to probe into the political, commercial and digital contexts in which visual cultures emerge and circulate, and to trace the potential of these cultures for political or social critique. Bart Barendregt is an associate professor at the Leiden Institute of Cultural Anthropology and Development Sociology.